State school catering in Italy during the COVID-19 pandemic: a qualitative study - Pagliarino, Elena (Frontiers in Sustainable Food Systems, 2024)
The complex value of school meals for children and families is well documented. In Italy, school cafeterias have been an instrument of social policy since the end of the Second World War. Thereafter, school cafeterias have acquired several functions in the areas of children's health and wellbeing, education, social inclusion, support to local and quality agriculture, and environmental sustainability. In particular, the goal of a nutritious and balanced diet has been emphasized in recent decades, since malnutrition and food insecurity have been increasing in Italian society. During the pandemic, Italy was the first European country to implement a nationwide lockdown and one of the high-income countries where schools closed for the longest period. In this work, we use in-depth interviews with representatives of the school catering service, both from the major catering companies and the biggest municipalities, to analyze what happened in the management of the Italian school catering service during the pandemic crisis. In addition, a review of public recommendations issued during the pandemic has made it possible to analyze their compliance with the state guidelines for school catering and food education. The results highlight how the system reacted extremely slowly to the crisis and how the measures taken led to a deterioration of the value that has always been attributed to state school cafeterias, especially in terms of children's food security and environmental sustainability.